Factors Associated with Periodontal Status and Treatment Needs Among Older People in Prosthodontic Department of a Non-Government Dental College: A Cross-Sectional Study (Journal of Dentistry and Allied Science, 2023)
Aim: The aim of the study was to assess factors associated with periodontal status and treatment needs among older people in prosthodontic department of a non-Government dental college Methods: Purposively selected sample consisted of 110 elderly adults aged 60 and older, seeking prosthodontic care. Demographic information was collected through a pretested structured questionnaire and periodontal condition assessed using checklist. Descriptive statistics were used to characterize demographic variables and to assess associations between periodontal health status and other factors by chi-square test and fisher’s exact test (p < 0.05) Results: The study examines the distribution of CPITN scores among elderly participants based on demographic factors. The results show diverse periodontal health status, ranging from healthy periodontium to pathological pockets of variable widths. No participants had healthy periodontium among various demographic variables. Females had 28.2% of supra and subgingival calculus, 13.6% had pathological pockets of 4-5mm, and 19.1% had pathological pockets of 6mm or greater. Men had 1.8%, and 16.4% displayed pathological pockets of 6mm or greater. Age group 65-70 had 12.7% of pathological pockets of 6mm or greater. Muslim, Hinduism, married, and primary education individuals had higher rates of bleeding on probing, supra and subgingival calculus, and pathological pockets. Business people had the highest percentage of people with pathological pockets of 6mm or greater. The study found significant associations (p